Competitive intensity value resonance antecedence for successful brand performance - Imroatul Khasanah; I Made Sukresna (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
This study aims to mediate the influence of the Brand Management System on Brand Performance by proposing a Competitive Intensity Value Resonance that mediates between the Brand Management System and the improvement of Brand Performance. Sample data from 160 food product SMEs in Central Java were used to test a model consisting of five hypotheses. The statistical test in this model uses five variables: Brand Management System, Marketing Orientation, Internal Branding, Competitive Intensity Value Resonance and Brand Performance. The results of the data show that Competitive Intensity Value Resonance has an important role in improving Brand Performance.